A case study of emergent environmental pedagogical content knowledge in a Fundisa for Change teacher professional development course - Brundrit, Susan (Rhodes University, Faculty of Education, Department of Education, 2018)
This study set out to explore and describe in the form of a qualitative case study, an iteration of a Fundisa for Change teacher professional development programme, in this case the Teaching Life & Living short course presented to seventeen teachers as part of their Advanced Certificate in Teaching (ACT) Senior Phase Natural Sciences, at the University of Cape Town. The focus of the research was on describing how the development of teacher environmental pedagogical content knowledge (PCK) was supported and constructed in the course. The Consensus Model of Teacher Professional Knowledge and Skill, an outcome of the 2012 PCK Summit, was used to define the concept of PCK and also contributed the concept of amplifiers and filters as processes that mediate the development of teacher PCK. The study drew on Borko's (2004) model of a professional development system, using the elements of course, teachers, facilitators and context as an analytical framework. Data generated included a teacher contextual profile questionnaire, audio-recordings of group work, course outputs and reflection and evaluation forms. Data analysis had two phases: the first phase concentrated on the development of analytic memos based on particular data sources whereas the second phase worked across data sources to present the evidence relating to each of the professional development system elements. The study found that teachers were supported in the development of their environmental PCK by the collaborative learning opportunities afforded by the course. Emergent PCK was organised according to five components: assessment knowledge; pedagogical knowledge; content knowledge; knowledge of learners; and, curricular knowledge. Emergent teacher learning ranged in specificity from general, to subject-specific, to domain-specific, and lastly to topic-specific knowledge. Teacher beliefs and orientations, prior knowledge and contexts brought into the professional development system were described as amplifiers and filters to teacher learning of PCK. In particular there were several contextual factors that emerged as themes from the data that had potentially filtering effects. Recommendations included that facilitators create an atmosphere conducive to collaborative learning, that evidence of learner conceptual understanding be examined during the course, that teachers be exposed to in-depth examples of canonical PCK and that more modelling of formative assessment strategies are presented.
Keywords: Career development -- South Africa; Environmental education -- South Africa; Teachers -- Training of --South Africa; Environmental education -- Study and teaching -- South Africa; Fundisa for Change